Mechanical, medical imaging and radiation properties of computed tomography-based kidney phantom exploiting textural analysis - Kamal, Izdihar (2022)
Medical imaging phantom has important role in mimicking the properties of human tissue for calibration, training, surgical planning, and simulation purposes. Through standardized quantitative imaging features, the phantom should be able to ascertain information that cannot be visually assessed via radiomic features. Thus, the stability and accuracy of the phantom play significant role in diagnostic imaging especially for the diagnostic performance. This work aimed to introduce an alternative and straightforward polymer-based phantoms with specific mechanical and dielectric properties at the utmost suitable for fabrication of computed tomography-based kidney phantom. To evaluate the influence of Hydrogen Silicone (HS) and water (H2O) on the compression strength, radiation attenuation properties, and Computed Tomography (CT) number of the blend Polydimethylsiloxane (PDMS) samples as to improve the pure PDMS properties. A polymer blend is a mixture of two and more polymers that have been blended to create a new material with different physical properties. Two phantom based materials; PDMS and silicone elastomer (SE), were investigated for their capabilities to address the requirements. Four samples were prepared with different compositions were studied, and denote as samples S1, S2, S3, and S4, which consisted of PDMS 100%, HS/PDMS 20:80, H2O/PDMS 20:80, and HS/H2O/PDMS 20:40:40, respectively. Radiation attenuation properties were evaluated using Phy-X/PSD (Turkey) and XCOM (NIST, USA). The elasticity and dielectric properties of phantom were superior for the blend HS/PDMS 20:80, besides the effective atomic number and linear attenuation coefficient has shown a similar pattern with human kidney tissue at intermediate energy level of 1.50 ⅹ 10-2 MeV to 1.5 MeV. PDMS is superior to SE in terms of tensile strength, flexibility, acceptable real part of the complex dielectric constant; Ɛr and conductivity which allows it to become a stable kidney phantom for CT scan purposes. Overall, HS/PDMS 20:80 with the use of a 120 kVp X-ray beam, the CT number quantified for sample measured 40 HU and had the highest Contrast-to-Noise Ratio (CNR) value better than pure PDMS. Therefore, the HS/PDMS 20:80 sample formulation exhibited the potential to mimic the human kidney as it has a similar dynamic and is higher in terms of stability as a medical phantom. In conclusion the blend PDMS as the material of choice to be used as a CT-based kidney phantom in terms of good agreement with compressive strength and radiation attenuation. Notably, the blend PDMS imitates human tissue more precisely and permits a wide range of possibilities for exploiting textural analysis and radiation dosimetry. Hence, it promises to be of value for use in both research and clinical settings for the CT modality as it is physically stable.